Development of technique capable of identifying different corrosion stages in reinforced concrete. (July 2015) - Qin, Lei; Ren, Hongwei; Dong, Biqin; Xing, Feng
Abstract: In order to develop an in-situ technique capable of identifying the transitions between different stages of corrosion in reinforced concrete, a new type of sensor was developed. The sensor uses piezoelectric elements to generate and receive ultrasonic waves, with a steel bar acting as a wave guide. In a corrosion acceleration test, the onset of corrosion was associated with a steady increase in the wave amplitude resulting from the accumulation of corrosion products at the concrete-steel interface. AE monitoring verified that cracks in the bonding layer act as obstacles to wave propagation, and their development stops the increase in the sensor signal. Bending tests showed that different type of cracks have different effects on signal propagation.